Sustainable human resource management relationship with the human resource risk reduction - Azra Ahmić; Selma Smajlović (Economic Review: Journal of Economics and Business, 2022)
Being exposed to tempestuous transformations and complexities in environment, contemporary enterprises are characterized by grand extent of suspense, unsteadiness and changeability. Increased number of risks, especially with regard to managing human resources, do not cause only temporarily troubles for standard business activities, but can be much more devastating - calling into question company's survival. The true objective of this paper was to discover if shaping human resource management in a sustainable manner (with long- term perspective) leads to human resource risk reduction. Grounded on the collected data by 65 human resource managers, hierarchical regression approach was employed as the analysis technique. The research outcomes disclosed that sustainable human resource management has a significant and positive relationship with human resource risks reduction. Multitude contributions were made by this study - initially, it validated of the sustainable human resource management research instrument; secondly, it upgraded the literature on sustainable human resource management and human resource risks; and finally, it empirically proved that there is a positive and significant relationship between sustainable human resource management and human resource risks reduction.
Keywords: M14; M54; O15; Q01; D81; 330; sustainable human resource management; human resource management; human resource risks